RANCANG BANGUN ALAT PASTEURISASI NON THERMAL DENGAN PULSED ELECTRIC FIELD (PEF) - Anggraini, Ika Novia; Simarmata, Elsara Krysti; Daratha, Novalio; Herawati, Afriyastuti; Rodiah, Yuli (UNIB Press, 2021)
ABSTRACTPackaged beverages have become a product that is very much on the market both internationally and nationally. In the process of making packaged beverages, in order to last longer the microbes in the drink must first be inactivated in order for the drink to last longer, the microbial inactivation process in the drink is called pasteurization. Convernsional pasteurization is done by heating the drink to be in production. But the high temperature of the drink can change the taste, color, and even nutrition of the drink. This is underpinning the non-thermal pasteurization process by using high voltage impulses (Pulsed Electric Field,PEF). PEF is a technology that utilizes high voltage DC to produce a field between two electrodes. Pateurization occurs when between electrodes there is milk that is flowed with high voltage DC. High voltage generation is performed using flyback transformers with voltage output up to 30 kV. In the pasteurization process given 6 voltage variations namely 5, 10, 12,5, 15, 20, and 30 kV. Pasteurization results are then tested in fmipa microbiology laboratory to find out the success of the tools that have been made. In each voltage variation it is obtained that all treatments have reached pasteurized milk quality standards based on SNI where at 5kV voltage variation can inactivat microbes up to 83.33%, voltage variation of 10kV can inactivat microbes up to 94.5%, At a voltage variation of 12.5 kV can inactivae microbes up to 83.6%, 15kV voltage variation can inactivae microbes up to 88.8%, while voltage variation of 20 kV can inactivae microbes up to 84.2% and at voltage variation 30 kV can inactivae microbes up to 84.8%.Key Words: PEF, Flyback Transformer, ZVS Driver, Pasteurization.